A Systematic Review of Benefit-Finding and Growth in Pediatric Medical Populations. (12th August 2021) - Kritikos, Tessa K; Stiles-Shields, Colleen; Winning, Adrien M; Starnes, Meredith; Ohanian, Diana M; Clark, Olivia E; del Castillo, Allison; Chavez, Patricia; Holmbeck, Grayson N
Abstract: Objective: This review synthesizes the literature on benefit-finding and growth (BFG) among youth with medical illnesses and disabilities and their parents. Specifically, we summarized: (a) methods for assessing BFG; (b) personal characteristics, personal, and environmental resources, as well as positive outcomes, associated with BFG; (c) interventions that have enhanced BFG; and (d) the quality of the literature. Methods: A medical research librarian conducted the search across PubMed, Scopus, PsycInfo, Google Scholar, and Cochrane Library. Studies on BFG among children ages 0–18 with chronic illnesses and disabilities, or the parents of these youth were eligible for inclusion. Articles were uploaded into Covidence; all articles were screened by two reviewers, who then extracted data (e.g., study characteristics and findings related to BFG) independently and in duplicate for each eligible study. The review was based on a systematic narrative synthesis framework and adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines (PROSPERO registration number: CRD42020189339). Results: In total, 110 articles were included in this review. Generally, BFG capabilities were present across a range of pediatric health conditions and disabilities. Correlates of both youth and parent BFG are presented, including personal and environmental resources, coping resources, and positive outcomes. In addition, studies describing interventions aimed at enhancing BFG are discussed, and a quality assessment of the included studies is provided. Conclusions: Recommendations are provided regarding how to assess BFG and with whom to study BFG to diversify and extend our current literature.